2019
DOI: 10.1016/j.asjsur.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phased education on attitudes toward organ donation and willingness to donate after brain death in an Asian country

Abstract: Phased education was effective overall, but it had a limited effect on changing the willingness to donate a family member's organs. It increased the consistency between people's attitudes toward organ donation and willingness to donate their own, or a family member's organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…These results were higher than those obtained by Park. [ 14 ] The systematic review [ 5 ] found that better knowledge and religious beliefs negatively impacted Koreans’ willingness and decision-making regarding organ donation. There was no statistically significant difference in terms of gender, age, or educational qualifications in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were higher than those obtained by Park. [ 14 ] The systematic review [ 5 ] found that better knowledge and religious beliefs negatively impacted Koreans’ willingness and decision-making regarding organ donation. There was no statistically significant difference in terms of gender, age, or educational qualifications in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Family members of South Korean patients in surgical ICUs found that 75% had positive attitudes toward organ donation, 60.9% were willing to donate their organs, and 38% were willing to donate the organs of their family members. [ 14 ] The more positive their attitudes toward organ donation were, the more significant their willingness to donate their family members’ organs. The prerequisite for family members to agree to organ donation was a prior understanding of the PBD’s medical condition and of brain death.…”
Section: Introductionmentioning
confidence: 99%
“…After education, their intention for both family members and their organs significantly increased. However, the intention of donating family member organs remained significantly lower than donating one's own organs ( 22 ). This can state that changing attitudes toward organ donation is a time-consuming process and it needs to be internalized overtime.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important as there were some misbeliefs about eye donation (e.g., no knowledge about the possibility of [research] donation, age as a limiting factor). Although there are studies showing that education regarding organ donation could increase willingness to donate organs [28,29], Lawlor et al [30] elaborated that personal, non-rational reasons are in fact particularly important in relation to the decision. Some patients are, even with transplant-related professional experience [31], still afraid of a disfigurement of their body; especially regarding skin, bone and corneal donation [24].…”
Section: Discussionmentioning
confidence: 99%